Hubungan Pengetahuan dengan Sikap Remaja Putri tentang Perubahan Fisik pada Masa Pubertas di MAN 1 Kabupaten Malang - Nurul Wafiah; Herawati Mansur; Sunaeni, Sunaeni (STIKES Columbia Asia Medan, 2025)
The importance of knowledge about physical changes during puberty because during this period there are many changes such as physical, psychological and social changes. Lack of knowledge about the changes that occur to them and why they occur can lead to embarrassment, anxiety or distrust. Can cause embarrassment, anxiety or distrust. Objective of this study was to determine the relationship between knowledge and attitudes of adolescent girls about physical changes at puberty. This study uses a correlation correlation analytic design with a cross sectional approach, population as many as 165 people, sampling using proportional random sampling technique, the number of samples was 50 respondents who met the inclusion criteria. sample of 50 respondents who met the inclusion criteria. Instrument the research instrument used a knowledge and attitude questionnaire. Data analysis using the spearman rank test. The results obtained p value 0.001 < α 0.05, it can be concluded that there is a relationship between knowledge and attitude of adolescent girls about physical changes during puberty at MAN 1 Malang Regency. Therefore, it is expected that adolescents can take the time to participate in youth health organization activities such as PMR or PIK-R in the school environment and seek information from various sources such as books, journals or magazines in order to increase their knowledge about physical changes during puberty. As for the research site, it is hoped that it can provide counseling evenly to students of MAN 1 Malang Regency.